Analisis Preferensi dan Partisipasi Civitas Akademik Institut Teknologi Kalimantan Dalam Pemilahan Sampah - Rahendaputri, Chandra Suryani; Endrawati, Budiani F.; Djafar, Alfian; Sutakin, Mariana Ulfah; Gunawan, Arie Indra; Hizbullah, Moh. Naufal; Armida, Gina; Savera, Arum; Dzulfiqa, Muhammad Rizky (LPPM ITK, 2024)
Solid waste management problems have become a common problem in Indonesia. Based on data from the Central Bureau of Statistics' Environmental Care Behavior Indicator in 2017, it shows that 58.32% of Indonesians do not sort their waste. Kalimantan Institute of Technology (ITK) is a campus that carries the concept of eco-campus. Waste segregation has been programmed, but in reality in the field, waste segregation is not running. Therefore, this study was conducted with the aim of knowing the preferences and participation of ITK academic community in waste segregation at ITK. The survey results showed that out of 380 respondents, although 90% had seen posters about waste segregation at ITK, only 57.6% stated that they had done waste segregation at ITK, which was mostly based on the factor of facilitating management both by ITK and at the landfill. For the other 44.2% of respondents who do not or only sometimes do waste segregation, it was found that the biggest factor that made them do so was based on the desire to segregate at the beginning, but when opening the trash can, the waste inside was already mixed.